Improving Teacher Competence through the Creation of Arduino-Based Gas Detection Media and Artificial Intelligence - Priyatna Hendriawan; Yani Nurareni; Ade Yeti Nuryantini; Tri Wahyu Agustina (International Journal of Learning Media on Natural Science (IJLENS), 2025)
The Indonesian government has begun to explicitly implement a deep learning approach through four main frameworks, namely pedagogical practices, learning environments, learning partnerships, and digital utilization. However, limitations in teacher skills and infrastructure, particularly in terms of technology, pose challenges to its implementation. This study aims to describe the process by which teachers at the Community Learning Center (PKBM) in Cibeber Subdistrict, Cianjur Regency, develop learning media based on an automated system using a simulator (Wokwi) and practical applications assisted by Arduino IDE. The creation of this media is also supported by artificial intelligence monitoring tools such as ChatGPT. This study employs a qualitative descriptive approach. Data collection was conducted through direct observation of 15 teachers from three PKBMs in Cibeber Subdistrict, Cianjur Regency. The research process focused on the development of a gas detection device by utilizing the four pillars of computational thinking: abstraction, decomposition, algorithmic thinking, and pattern recognition. Data analysis was conducted using the Miles & Huberman qualitative data analysis method, which includes data collection, data reduction, data presentation, and drawing conclusions. The research results indicate that teachers were able to follow all stages of tool development, achieving the following indicators: abstraction (70%), decomposition (85%), algorithmic thinking (78%), and pattern recognition (81%). Although most teachers come from non-science backgrounds and have no prior programming experience, they successfully designed gas detection tools (LPG, alcohol, smoke, and carbon monoxide) and adapted their experience to create a smart parking system project. This study demonstrates that the use of artificial intelligence, such as ChatGPT, along with simulators and hands-on practice, can bridge the technical limitations of teachers. This supports teachers' creativity and ability to develop technology-based contextual learning materials in a more independent and innovative manner.